Institution building and leadership in Africa - Wohlgemuth, Lennart, 1940-; Carlsson, Jerker, 1950-; Kifle, Henock (Nordiska Afrikainstitutet ; Distributor in North America, Transaction Publishers, 1998)
"This anthology aims at increasing the understanding of current management practices in Africa and of the challenges faced in building institutions. It attempts to provide, on the basis of varied theoretical and historical perspectives, a richer understanding of the conditions faced by the leaders in Africa and reviews experiences of management, leadership and institution building through a number of case studies where the authors relate their own and others experiences in different sectors and countries."--BOOK JACKET. "It is directed at an African readership aiming to contribute to an increased understanding of the difficult and long-term work of developing good management and institutions in Africa, but also at the donor community where it is hoped to encourage the emergence of more effective assistance in this area."--Jacket